Modern Christianity: The Swiss reformation - Schaff, Philip; (1819-1893) (U.S.A, 1958)
Philip Schaff wrote one of the finest histories of the church available. His eight-volume work, which covers Christian history from the apostles to the Swiss Reformation, incorporates a discussion of ideas and ideals throughout the history of the church with the requisite facts and figures for each period of history. Each volume contains maps, charts, notes, bibliographies, and an index.
Keywords: Church history